(untitled) (Journal for the Study of Religion and History (JSRH), 2026)
Throughout the interpretive history of the Song of Songs, the theme of love has undergone successive transformations shaped by shifts in interpretive agents and methodologies. In early rabbinic interpretations, the theme of love was inscribed into the framework of sacred history. This process was rooted in two interconnected developments: first, the canonization of the Song of Songs within the Hebrew Bible, which invested it with sacred authority; and second, the rabbinic practice of conducting verse-by-verse parallel interpretations that anchored the text in the Torah. Early rabbinic interpretations transcended the Song of Songs’ literal depictions of love, reconfiguring its secular themes into commemorations of sacred history and articulations of the divine-human relationship. The love portrayed in the text, functioning as a textual thread, is intertwined with sacred history as an interpretive thread: rabbinic exegesis employed the former as a vehicle for religious meaning, using it to foreground the latter as the text’s true theological core. By analyzing the Mishnah and the midrashic work Shir Ha-Shirim Rabbah, this article elucidates how sacred history absorbs and reframes the theme of love within its narrative.